A study of perception of racial tolerance in Kuala Penyu / Aprilynn Esther James - James, Aprilynn Esther (2010)
Concern about multiracial country as Malaysia, a lot of issues arises regarding to this matter. Inter-marriages is one of the issues that always been a problem by spouse with different races or ethnic. The background of Malaysia's multiracial was shown from the stone age where the arrival of immigrants in Borneo and Peninsular Malaysia."[Malayness, is being a bumiputera in Malaysia. The constitution specifies that Malay habitually speaks Malay, is a Muslim, and practices the Malay culture. Thus, two features of being Malay are cultural. Ethnicity is the key to any discussion of identity in Malaysia. Malays are the product of two waves of migration from Yunnan in China. Stone Age migrants left traces of their culture in Peninsular Malaya and crossed the then land bridge to Borneo. Tribal elements continue to exist in the jungles and mountains of the peninsula, and their descendants were once known collectively as the 'Wild Men of Borneo' they are known as the Kadazan, the Dusun in Borneo and are bumiputera also." (Ronald D. Palme, 2007)A. Thus Malaysia being a multiracial country with different ethnic and culture living together using one rule that have been implemented by Malaysian government since its formation.